Relationship-building around a policy decision-support tool for urban health. Issue 1 (23rd August 2021) - Deloly, Clément; Roue-le Gall, Anne; Moore, Gemma; Bretelle, Lucy; Milner, James; Mohajeri, Nahid; Osrin, David; Salvia, Giuseppe; Symonds, Phil; Tsoulou, Ioanna; Zimmermann, Nici; Wilkinson, Paul; et al.
Contemporary challenges linked to public health and climate change demand more effective decision-making and urban planning practices, in particular by taking greater account of evidence. In order to do this, trust-building relationships between scientists and urban practitioners through collaborative research programmes is required. Based on a policy-relevant research project, Complex Urban Systems for Sustainability and Health (CUSSH), this project aims to support the transformation of cities to meet environmental imperatives and to improve health with a quantitative health impact assessment. A case study in Rennes, France, focuses on the role of a policy decision-support tool in the production and use of knowledge to support evidence-informed decision-making. Although the primary objective of informing decision-making through evidence-based science is not fulfilled, the use of a decision-making support tool can lay the foundations for relationship-building. It can serve as a support for boundary-spanning activities, which are recognised for their effectiveness in linking science to action. This case study illustrates that the path of knowledge transfer from science to policy can be challenging, and the usefulness of using models may not be where it was thought to have been. Practice relevance: The requirements for an effective policy-relevant research programme depend on the establishment of trust. An analysis of the evolution of relationships between cities' practitioners and scientists shows the need to establish relationships between stakeholders involved in this kind of research. Even if it does not directly support the implementation of transformational policies for health and sustainability, the use of a decision-making support tool can become essential in building trust relationships and later have ripple effects to achieve its primary goals. Moreover, a dedicated team has a key role to facilitate the links between scientists and cities practitioners—to boundary span. Finally, this paper adds to a growing body of work reflecting upon the success of policy–research partnerships.